1996
DOI: 10.1006/obhd.1996.0013
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Regret Aversion: Effects of Expected Feedback on Risky Decision Making

Abstract: Consequences of regret aversion: effect of expected feedback on risky decision making Zeelenberg, M.; Beattie, J.; van der Pligt, J.; de Vries, N.K. Published in:Organizational Behavior and Human Decision Processes DOI:10. 1006/obhd.1996.0013 Link to publication Citation for published version (APA):Zeelenberg, M., Beattie, J., van der Pligt, J., & de Vries, N. K. (1996). Consequences of regret aversion: effect of expected feedback on risky decision making. Organizational Behavior and Human Decision Processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
278
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(298 citation statements)
references
References 30 publications
18
278
2
Order By: Relevance
“…They value it in both an absolute sense (the favorable aspects outweigh the unfavorable aspects) and in a relative sense (as compared to other commonly experienced negative emotions). This is a surprising finding given the assumption of the aversiveness of regret, both tacit and implicit, that underlies much prior research, particularly work centering on biased decision-making (e.g., Bell 1982; Connolly and Butler 2006;Zeelenberg et al 1996). Indeed, recent depictions of the functional value of regret (e.g., Zeelenberg 1999;Zeelenberg and Pieters 2007) and the willingness of individuals to risk the experience of regret (van Dijk and Zeelenberg 2007) have been theoretically striking precisely because regret was previously assumed to be undesirable, both in terms of its biasing effect on rational decision-making and also its link to depression (Lecci et al 1994;Markman and Weary 1998;Monroe et al 2005).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…They value it in both an absolute sense (the favorable aspects outweigh the unfavorable aspects) and in a relative sense (as compared to other commonly experienced negative emotions). This is a surprising finding given the assumption of the aversiveness of regret, both tacit and implicit, that underlies much prior research, particularly work centering on biased decision-making (e.g., Bell 1982; Connolly and Butler 2006;Zeelenberg et al 1996). Indeed, recent depictions of the functional value of regret (e.g., Zeelenberg 1999;Zeelenberg and Pieters 2007) and the willingness of individuals to risk the experience of regret (van Dijk and Zeelenberg 2007) have been theoretically striking precisely because regret was previously assumed to be undesirable, both in terms of its biasing effect on rational decision-making and also its link to depression (Lecci et al 1994;Markman and Weary 1998;Monroe et al 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Regret is additionally problematic because of its biasing effect on decision-making, an idea central to regret theories in economics (e.g., Bell 1982; Connolly and Butler 2006). At a more basic level, regret (like any negative emotion) is intrinsically aversive, hence individuals are motivated to avoid it, even if this means sacrificing an objectively superior reward (Zeelenberg et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point was illustrated by Zeelenberg, Beattie, van der Pligt and de Vries (1996) in three hypothetical gambling experiments which also manipulated feedback about foregone alternatives. In each of three conditions participants could choose a risky or safe gamble and in all three conditions they expected to receive feedback about their chosen option.…”
Section: Anticipated Regretmentioning
confidence: 98%
“…A number of experimental studies have found that regret does influence decision-making (Bleichrodt, Cillo, & Diecidue, 2007;Cooke, Meyvis, & Schwartz, 2001;Janis & Mann, 1977;Sorum et al, 2004;Wolfson & Briggs, 2002;Zeelenberg, 1999;Zeelenberg, Beattie, van der Pligt, & de Vries, 1996) and can explain various economic phenomena (Smith, 1996;Tsiros & Mittal, 2000;Braun & Muermann, 2004;Dodonova & Khoroshilov, 2005;Muermann, Mitchell, & Volkman, 2006;Cooke et al, 2001).…”
Section: Regret and Rejoicingmentioning
confidence: 99%